Phytochemistry of tinospora cordifolia - Kumar, Brijesh; Bajpai, Vikas; Kumar, Nikhil (Boca Raton : CRC Press, 2020)
Tinospora cordifolia stem is used as a tonic, vitalizer, and as a remedy for metabolic disorders to treat allergies, diabetes, dysentery, jaundice, heart diseases, leprosy, rheumatoid arthritis, skin diseases, and urinary disorders. It shows anti-inflammatory, analgesic, antipyretic actions and immunosuppressive effects. This book focuses on providing gender and geographical location-based differences in the phytoconstituents of T. cordifolia by the liquid chromatography mass spectrometric method. These methods have potential use in the quality control of T. cordifolia and the screening of herbal preparations. Features: Compilation of ayurvedic features of one of the most important plants of the Indian system of medicines. Useful for all ayurvedic practitioners, researchers, faculty, students, and herbal product manufacturers. Application of advance hyphenated LC-MS techniques for variation study in phytoconstituents.
OCLC-licensed vendor bibliographic record.
Keywords: Menispermaceae; Menispermaceae -- Therapeutic use; Materia medica, Vegetable; Botanical chemistry; MEDICAL / Pharmacology; SCIENCE / Chemistry / General